Le Nhat Phuong
14 tháng 9 2017 lúc 20:32

Nguyễn Ngọc Hân 0606

x-2) + x^2.(2-x)=0 <=> 4.(x-2) + x^2.[-(x-2)]=0 <=> 4.(x-2) - x^2.(x-2)=0 <=> (x -2)*(4 - x^2) = 0 <=> x = 2 { x^2= 4 <=> x = 2 { x= 2 hoặc x = -2 <=> x = 2 { x = -2

Bình luận (0)
Phạm Văn Tiến
14 tháng 9 2017 lúc 20:46

bài này vô nghiệm ngăn bạn 

Bình luận (0)
Tú Nguyễn Minh
14 tháng 9 2017 lúc 20:49

Ta có: 

 ( x+1 ) (x+2)2 + x2 (4-x) = 0    

 ( x+1 ) (x2 - 2.2x + 22 )+ 4x2 - x3 = 0

 x- 4x2  + 4x  + x2 - 4x + 4 + 4x2 - x3 = 0 

                                                   x2 +4 = 0

<=>                                                   x2 = 4

=>                                                     x = +- 2

Bình luận (0)

Các câu hỏi tương tự

Khoá học trên OLM của Đại học Sư phạm HN

Loading...

Khoá học trên OLM của Đại học Sư phạm HN